PENGARUH PELAKSANAAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris pada SKPD Kota Bandung) - DIMAS RUSVIANTO; SRI MULYANI; INDRI YULIAFITRI (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2018)
AbstractLocal government financial management should be based on good governance,which is transparent and accountable financial management. Thephenomenon that occurred in the Local Government of Bandung City is thefinancial management that is still less good compared to other localgovernments in Indonesia which can be seen from the opinion of the FinancialAuditing Board Agency (BPK) With Fair Exception (WDP). Inadequateimplementation of the Government's Internal Control System (SPIP) isreflected in many recurring findings from year to year, with no explanationthat the findings have been followed up by the local government. In addition,the weak competence of human resources in applying the Government'sInternal Control System also contributed to the failure of the WTP opinion astargeted by the central government. The method used in this research isdescriptive statistical method with primary data type through questionnaire.The result of this research is the Implementation of Government InternalControl System (SPIP) and Human Resource Competence (HR) have asignificant positive effect on the quality of local government financialstatements of Bandung.